Prevalence of Methicillin-Resistant Staphylococci on a Farm: Staff can Harbour MRS When Animals do Not - Aquino, G. de V. [UNESP]; Maluta, R. P. [UNESP]; Ávila, Fernando Antonio de [UNESP] (Wiley-Blackwell, 2012)
The aim of this work was to establish the prevalence of methicillin-resistant Staphylococci (MRS) in the animals and staff of a teaching and research farm. Samples of dairy cattle (36), beef cattle (26), sheep (19), horses (21), pigs (23), goats (23) and humans (13) were collected and screened for the presence of MRS. The detection of mecA gene was performed by PCR to determine the resistance of the samples to methicillin. Antimicrobial-resistance testing to penicillin, meropenem, ceftriaxone, cephalothin, oxacillin, levofloxacin, enrofloxacin, chloramphenicol, ciprofloxacin, gentamicin, clindamycin, erytromycin, linezolid, sulfamethoxazole/trimethoprim, tetracycline, doxycycline and vancomycin was performed on the mecA+ isolates. From the 161 samples, four methicillin-resistant coagulase-negative Staphylococci (MRCoNS) were isolated from human beings (31%), whereas none was isolated from animals (0%). No methicillin-resistant Staphylococcus aureus (MRSA) were isolated. All of the MRCoNS isolates from this work presented different antimicrobial resistance patterns. MRCoNS may be present in humans associated with animals while not present in the animals. Selective pressure outside of the farm and a lack of MRCoNS transmission between humans and animals may be responsible for this lack of correlation.
Keywords: Farm animals; MRSA; MRS; mecA; resistance to methicillin; Staphylococcus spp